Molecular Characterization, Plasmid Profiling and Antibiotic Sensitivity of Vibrio Parahaemolyticus from Shellfish, Hospital Wastewater and Human Stools in Padang, West Sumatera, Indonesia - Adly, Marlina (2007)
Vibrio parahaemolyticus, a gram-negative marine bacterium, is an important food borne pathogen causing gastroenteritis, particularly in areas with high seafood consumption. A total of 29 human stools, 20 hospital wastewater and 120 shellfish samples from Padang area in Sumatera, Indonesia were examined in this study. Purple coloured colonies presumptive of V. parahaemolyticus from preliminary screening process on CHROMagarTM Vibrio were selected and confirmed as V. parahaemolyticus using polymerase chain reaction by the amplification of the toxR fragment at 368 bp. Of the 169 samples, 42 (24.8%) from shellfish (13 from B. violacae; 20 from C. moltkiana; 9 from F. ater), 13 (7.7%) from hospital wastewater and 12 (7.1%) from human stool samples were found to be contaminated with V. parahaemolyticus. The presence of virulence genes (tdh and trh) of all toxR positive isolates were carried out using PCR. None of the isolates possesed the trh gene. However, 18 isolates from the human stools, hospital wastewater and shellfish (raw B. violacae and cooked C. moltkiana) samples harboured the tdh gene. A total of 97 V. parahaemolyticus isolates from human stools, hospital wastewater and shellfish samples were examined for their resistance to 15 antibiotics. Majority of the isolates (70%) were resistant to more than nine antibiotics in this study. The general, a V. parahaemolyticus isolates are resistant to sulfamethoxazole (100%), rifampin (95%) and tetracycline (75%) and sensitive to norfloxacin (96%). None of the isolates from human stools were resistant to ampicillin. Overall, all isolates were sensitive to chloramphenicol and floroquinolones (ciprofloxacin and norfloxacin agents). Eighty three isolates were examined for the existence of plasmids. A total of 61 (74.7%) V. parahaemolyticus isolates were plasmid-free. Nine isolates (11.8%) harboured the 9.4 kb plasmid. All of the remaining isolates carried plasmid DNA with sizes ranging from 2.3 kb to >23 kb. A large plasmid of 23 kb was evident in the plasmid harboring strains and appeared as the only plasmid in three isolates. RAPD profiling with three primers (OPAR3, OPAR4 and OPAR8) produced four major clusters (R1, R2, R3 and R4) and 7 minor clusters (I, II, III, IV, V, VI and VII). ERIC PCR using primer 1R and 2R produced two major clusters (E1 and E2) and ten minor clusters (A, B, C, D, E, F, G, H, I and J). All the dendrograms were being constructed utilizing the RAPDistance software package based on the data retrieved from the presence or absence of banding pattern. Both the molecular techniques of RAPD and ERIC genotyping showed most strains (? % and ?% respectively) from different samples and different locations revealed very high genetic variability in the microbial population studied. Combining the results of RAPD with ERIC apparently provides a degree of discrimination that should be adequate for identifying possible origins of V. parahaemolyticus contamination and for establishing relationships between isolates. Both methods showed a great diversity among the isolates of this species and could represent useful tools for the epidemiological typing of V. parahaemolyticus from Indonesia. Hence, the problem of the contamination of foods by V. parahaemolyticus, like many other food safety issues in diverse society, reflects the challenges of larger public health systems of care. Addressing this problem will require a combined approach including improved access, legislation, education, and culturally relevant patient-provider interactions.